ANALISIS POLA PENGOBATAN HIPERTENSI PADA PASIEN RAWAT JALAN DI PUSKESMAS JANAPRIA, LOMBOK TENGAH TAHUN 2023 - Annisaturrahmah Himawan (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Hypertension Is A Non-Communicable Disease With Increasing Prevalence And Is A Major Risk Factor For Cardiovascular Diseases. Proper And Continuous Treatment Is Essential, Especially At Primary Healthcare Facilities Such As Public Health Centers. This Study Aimed To Analyze The Pattern Of Hypertension Treatment In Outpatients At Janapria Public Health Center, Central Lombok, In 2023. This Research Used A Descriptive Method With A Retrospective Approach Based On Patients’ Medical Records. The Results Showed That The Most Commonly Used Antihypertensive Drugs Were Calcium Channel Blockers And Ace Inhibitors, Either As Monotherapy Or Combination Therapy. Most Treatments Were Consistent With Hypertension Management Guidelines, Although Variations In Treatment Patterns Were Still Observed. In Conclusion, The Hypertension Treatment Pattern At Janapria Public Health Center Tends Toward Rational Drug Use; However, Continuous Evaluation Is Needed To Improve Healthcare Quality.